Health visiting in England: The impact of the COVID‐19 pandemic. Issue 4 (31st January 2022) - Morton, Alison; Adams, Cheryll
Abstract: This focused review of evidence considers the impact of the pandemic in 2020 on families with children under 5 years in England, and the health visiting (HV) service that supports them. . Data were drawn from national surveys of health visitors (HVs) and parents, a freedom of information request of employers, published research, and national data. Framework analysis and triangulation, using the Key Elements of an effective HV service, were used to categorize the key findings. The findings from the review indicate that the impacts of the pandemic were wide‐ranging and disproportionately affected the most disadvantaged families, increasing demand for HV support. HVs' ability to respond was compromised due to national policy decisions to partially stop the service and variations in local implementation including the redeployment of HVs, pre‐existing workforce capacity issues, and the effectiveness of innovations to identify and support vulnerable families. The pandemic exacerbated factors that can lead to poorer outcomes for families. Key learning from the pandemic response, including the need to prioritize the HV service, must be acted upon to reduce ongoing impacts now and ensure that the service is equipped for future emergencies.